Odstiranje slovenskih krajevnih imen - Torkar, Silvo (Glasnik Slovenskega etnološkega društva, 2016)
Contrary to previous etymological explanations, which derived the place name Gorjansko from the common noun gorjani, this text reconstructs the original form *Dvorjansko as derived from the demonym *Dvorjane. While previously there has been no convincing explanation for the place name Imeno this article provides its etymology, on the basis of historical records and dialectal forms for a demonym and adjectival derivative, as *Jamljane.
Keywords: Slovene; slovenščina; imenoslovje; onomastics; onomastika; krajevna imena; etimologija; etymology; Gorjansko; Imeno